FDI and Economic Development in China's Minority Areas : Challenges in Policy and Practice - Blachford, Donyan (2012)
This paper focuses on China's policy and practices around foreign direct investment (FDI) and the impact of these on minority economic development. It provides a clear picture of China's current FDI policies, identifies the major changes that have taken place, and illustrates how the policies are no longer optimal. It is argued that sharing the fruits of the country's recent economic growth with the people of minority regions is not only important for the well-being of these marginalized populations, but is also crucial for the political stability, social and economic development, and international influence of China as a whole.